The Influence of Transformational Leadership and Work Ethic on Employee Performance through Organizational Commitment - Fatoni, Hamdan Arif; Mulyono, Sugeng; Nasir, Jamal Abdul (Electronic Journal of Education, Social Economics and Technology, 2024)
This study aims to test and analyze the effects of transformational leadership, work ethic, and organizational commitment on employee performance. Additionally, it examines the influence of transformational leadership and work ethic on organizational commitment and explores the mediating role of organizational commitment in these relationships. The research was conducted among employees of the Al-Rifa'ie Islamic Boarding School Cooperative in East Java, using a survey-based explanatory research design. A saturated sampling technique was employed, with all 83 employees participating. Data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS).The findings reveal that transformational leadership does not significantly affect employee performance, while work ethic and organizational commitment have significant positive impacts. Transformational leadership also does not significantly influence organizational commitment, but work ethic does. Furthermore, organizational commitment fails to mediate the relationship between transformational leadership and employee performance. However, it successfully mediates the effect of work ethic on employee performance.This research highlights the complex interrelations among transformational leadership, work ethic, and organizational commitment and their influence on employee performance. It underscores the importance of fostering a strong work ethic and enhancing organizational commitment to achieve optimal employee outcomes. Cooperatives should develop strategic approaches to transformational leadership, work ethic, and organizational commitment to boost performance effectively. The study also contributes theoretically by expanding the understanding of these variables and the mediating role of organizational commitment within a cooperative context.